Possible Bioenergetic Biomarker for Chronic Cancer-Related Fatigue. Issue 6 (November 2021) - Hsiao, Chao-Pin; Daly, Barbara; Chen, Mei-Kuang; Veigl, Marty; Dorth, Jennifer; Ponsky, Lee Evan; Hoppel, Charles
Abstract : Background: Cancer-related fatigue (CRF) is a highly prevalent, debilitating, and persistent symptom experienced by patients receiving cancer treatments. Up to 71% of men with prostate cancer receiving radiation therapy experience acute and persistent CRF. There is neither an effective therapy nor a diagnostic biomarker for CRF. This pilot study aimed to discover potential biomarkers associated with chronic CRF in men with prostate cancer receiving radiation therapy. Methods: We used a longitudinal repeated-measures research design. Twenty men with prostate cancer undergoing radiation therapy completed all study visits. CRF was evaluated by a well-established and validated questionnaire, the Patient-Reported Outcomes Measurement Information System for Fatigue (PROMIS-F) Short Form. In addition, peripheral blood mononuclear cells were harvested to quantify ribonucleic acid (RNA) gene expression of mitochondria-related genes. Data were collected before, during, on completion, and 24 months postradiation therapy and analyzed using paired t -tests and repeated-measures analysis of variance. Results: The mean of the PROMIS-F T score was significantly increased over time in patients with prostate cancer, remaining elevated at 24 months postradiation therapy compared to baseline. A significant downregulated BC1 ubiquinol-cytochrome c reductase synthesis-like ( BCS1L ) was observed over time during radiation therapy and at 24 months postradiation therapy. An increased PROMIS-F score was trended with downregulated BCS1L in patients 24 months after completing radiation therapy. Discussion: This is the first evidence to describe altered messenger RNA for BCS1L in chronic CRF using the PROMIS-F measure with men receiving radiation therapy for prostate cancer. Conclusion: Our results suggest that peripheral blood mononuclear cell messenger RNA for BCS1L is a potential biomarker and therapeutic target for radiation therapy-induced chronic CRF in this clinical population.